ORGANISASI SEBAGAI ARENA KEKUASAAN POLITIK - Yosar Kardiat (Jurnal Pallangga Praja (JPP), 2022)
This article discusses the organization as a vehicle (arena) in political power. Organization andpolitics become one unit in the use of power in Indonesia. In essence, the use of power in politicsaims to regulate the interests of the community as a whole, not for personal or group interests.For this reason, the limitation of power is very necessary in order to grow public trust in those inpower and create justice and comfort in life. Seeing organizational activities as political activitiesis a refresher on the understanding of organizational life which has always been dominated by aninstrumental perspective, whose analysis ignores the motives and interests of the actors involvedin the organization.